Reducing the impact of Auger recombination in quasi-2D perovskite light-emitting diodes - Yuanzhi Jiang (Nature Portfolio, 2021)
Designing efficient perovskite light-emitting diodes remains a challenge due to the strong Auger recombination and resulting Joule heating. Here, the authors propose polarizable p-fluorophenethylammonium to generate quasi-2D perovskites with reduced binding energy developing perovskite light-emitting diodes with a peak EQE of 20.36% and a maximum luminance of 82,480 cdm-2.